The forgotten frontier a history of the sixteenth century Ibero-African frontier - Hess, Andrew C. (Publications of the Center for Middle Eastern Studies, 2010)
The sixteenth-century Mediterranean witnessed the expansion of both European and Middle Eastern civilizations, under the guises of the Habsburg monarchy and the Ottoman empire. Here, Andrew C. Hess considers the relations between these two dynasties in light of the social, economic, and political affairs at the frontiers between North Africa and the Iberian peninsula.